Antimicrobial Peptide Conjugated on Graphene Oxide-Containing Sulfonated Polyetheretherketone Substrate for Effective Antibacterial Activities against Staphylococcus aureus - Selvaraj Rajesh Kumar; Chih-Chien Hu; Truong Thi Tuong Vi; Dave W. Chen; Shingjiang Jessie Lue (MDPI AG, 2023)
In the present study, the antimicrobial peptide nisin was successfully conjugated onto the surface of sulfonated polyetheretherketone (SPEEK), which was decorated with graphene oxide (GO) to investigate its biofilm resistance and antibacterial properties. The PEEK was activated with sulfuric acid, resulting in a porous structure. The GO deposition fully covered the porous SPEEK specimen. The nisin conjugation was accomplished using the crosslinker 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) through a dip-coating method. The surface micrographs of the SPEEK-GO-nisin sample indicated that nisin formed discrete islets on the flat GO surface, allowing both the GO and nisin to perform a bactericidal effect. The developed materials were tested for bactericidal efficacy against Staphylococcus aureus (S. aureus). The SPEEK-GO-nisin sample had the highest antibacterial activity with an inhibition zone diameter of 27 mm, which was larger than those of the SPEEK-nisin (19 mm) and SPEEK-GO (10 mm) samples. Conversely, no inhibitory zone was observed for the PEEK and SPEEK samples. The surface micrographs of the bacteria-loaded SPEEK-GO-nisin sample demonstrated no bacterial adhesion and no biofilm formation. The SPEEK-nisin and SPEEK-GO samples showed some bacterial attachment, whereas the pure PEEK and SPEEK samples had abundant bacterial colonies and thick biofilm formation. These results confirmed the good biofilm resistance and antibacterial efficacy of the SPEEK-GO-nisin sample, which is promising for implantable orthopedic applications.